In vitro antifungal susceptibility of Candida spp. oral isolates from HIV-positive patients and control individuals - Graziella Nuernberg Back Brito; Aline Cássia Inocêncio; Sílvia Maria Rodrigues Querido; Antonio Olavo Cardoso Jorge; Cristiane Yumi Koga-Ito (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Oropharyngeal candidiasis is the most common fungal infection among HIV-positive patients. This condition can be treated with either systemic or topical antifungal agents; treatments are usually indicated empirically on the basis of clinical data. The knowledge of in vitro antifungal susceptibility is important to determine correct therapeutic guides for the treatment of fungal infections. Therefore, the objective of this study was to determine the antifungal susceptibility profile of oral Candida isolates from HIV-positive patients and control individuals. Amphotericin B, fluconazole, flucytosine, nystatin and ketoconazole were tested according to the methodology of microdilution proposed by the Clinical and Laboratory Standards Institute (CLSI); results were recorded in values of minimal inhibitory concentration (MIC). A total of 71 Candida isolates from HIV-positive patients were examined with the following species represented: C. albicans (59), C. tropicalis (9), C. glabrata (1), C. guilliermondii (1) and C. krusei (1). A total of 15 Candida isolates were evaluated from control individuals comprised of 11 C. albicans and 4 C. tropicalis samples. Our results demonstrated that the tested antifungal agents showed good activity for most isolates from both groups; however, variability in MIC values among isolates was observed.